KAJIAN TERHADAP PELAKSANAAN PELINDUNGAN LAHAN PERTANIAN PANGAN BERKELANJUTAN (PLP2B) DI KABUPATEN SERDANG BEDAGAI DENGAN PENDEKATAN PARTICIPATORY ACTION RESEARCH (PAR) - Agusmidah; Iswan Kaputra (Jurnal Hukum Samudra Keadilan, 2023)
Declining agricultural land and poor conditions, as well as the impact of food shortages, are clearly contrary to Indonesia's commitment to the Sustainable Development Goals (TPB/SDGs). SDGs goal number 2 is to end hunger, achieve food security, improve nutrition and promote sustainable agriculture, in line with Indonesia's development priorities. Regional Regulation No. 1 of 2015 concerning PLP2B in Serdang Bedagai Regency has been enacted, but the fact is that paddy fields have decreased from 2017 to 2018, namely an area of ​​38,725 ha to 36,168 ha (a decrease of around 2,500 ha). The legal issue raised is whether the implementation of Regional Regulation No. 1 of 2015 for The Protection Of Sustainable Food Agricultural Land (PLP2B) in Serdang Bedagai district has been effective so as to encourage the achievement of sustainable development goals (SDGs). The Participatory Action Research (PAR) approach is used because the respondents are farmers so that the methods of sharing stories, in-depth interviews and focus group discussions are more likely to be carried out, participants/informants have more opportunities large share their experiences, ideas, and reflections more openly. In general, Regional Regulation No. 1 of 2015 concerning Protection of Sustainable Food Agricultural Land (PLP2B) in Serdang Bedagai has not been properly implemented. Formation of the Implementation Planning Team or Working Group has just been formed and at the time this report was prepared, the team only got to the first meeting.